Hamdolok - Umi Abdullah (Siri mengenal budaya, 2003)
Hamdolok is believed to have originated from the Middle East, where it is performed by Bedouins to celebrate the Prophet Muhammad's birthday. In Malaysia, hamdolok is best known in Batu Pahat, Johor. The performance includes local elements such as the use of gendang (drum) and gambus (a lute of Arabic origin), and featuring traditional Malay opera (bangsawan) together with Arabic style singing and dancing called zapin.